Assessment of Serum Free Light Chains as a Marker of Diabetic Nephropathy; A Cross-Sectional Study in the Kumasi Metropolis - Sorvor, Elizabeth; Owiredu, William K. B. A.; Okyere, Perditer; Annani-Akollor, Max Efui; Donkor, Sampson; Bannor, Richard; Sorvor, Felix B.K.; Ephraim, Richard K.D. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aims Although traditional tests such as serum urea, creatinine, and microalbuminuria have been widely employed in the diagnosis of diabetic nephropathy, their sensitivity and accuracy are limited because kidney damage precedes the excretion of these biomarkers. This study investigated the role of serum free light chains in the disease manifestation of diabetic nephropathy. Materials and Methods Using a cross-sectional design we recruited 107 diabetes mellitus out-patients who visited the Diabetes and Renal Disease Clinics at the Komfo Anokye Teaching Hospital, Manhyia District Hospital, and Suntreso Government Hospital all in Ghana from November 2019 to February 2020. Five (5) mls of blood was collected from each participant and analyzed for fasting blood glucose (FBG) urea, creatinine, immunoglobulin free light chains. Urine samples were obtained and analyzed for albumin. Anthropometric characteristics were also measured. Data were analyzed using descriptive analysis, analysis of variance (ANOVA) test, Tukey HSD post hoc, and Kruskal Wallis test. Chi-squared test was used to examine if there are significant associations with the indicators of interest. In addition, Spearman’s correlation was used to test for associations between appropriate variables. Receiver operating characteristic analysis (ROC) was also performed to assess the diagnostic performance of free light chains. Results The mean age of studied participants was 58.2 years (SD: ± 11.1), 63.2% were females and most of the participants were married (63.0%). The mean FBG of the studied participants was 8.0mmol/L (SD: ± 5.86), and the average duration of diabetes mellitus (DM) was 11.88 years (SD: ± 7.96). The median serum Kappa, Lambda, and Kappa: Lambda ratios for the studied participants were 18.51 (15.63-24.18), 12.19(10.84-14.48), and 1.50(1.23-1.86) respectively. A positive correlation was observed between albuminuria and; Kappa (rs=0.132; p=0.209), and Lambda (rs=0.076; p=0.469). However, a negative correlation was observed between albuminuria and K: L ratio (rs=-0.006; p=0.956). Conclusions The current study observed an increasing trend in the levels of free light chains and degree of diabetic nephropathy, although not statistically significant. The exploration of serum free light chains as a better marker of diabetic nephropathy showed very promising results but further studies are required to elucidate its predictive value as a diagnostic tool for diabetic nephropathy.